TROLLing - The Tromsø Repository of Language and Linguistics: Scope and operation of an open repository for linguistic data - Andreassen, Helene N.; Conzett, Philipp; Janda, Laura Alexis; Longva, Leif; Nesset, Tore; Høydalsvik, Stein; Odu, Obiajulu (2017)
Poster presentation from Møte om norsk språk (MONS) 17, 22-24 November 2017, Os, Bergen.